Reaching the Peripheral Regional Growth Centre - Jörgen Gren (European Journal of Spatial Development)
The centre-periphery concept can be used in a wide variety of ways, not the least to extract funding, as is shown in the Nordic case. More importantly, the centre-periphery concept is at the very heart of most national regional policies and aid schemes as well as being at the heart of the EU’s cohesion/convergence efforts undertaken in the framework of the Structural and cohesion funds. It then follows that the goal of virtually all studies concerning the centre-periphery paradigm has been to assess whether there is convergence or divergence in development between the centre and the periphery, and what are the factors associated with the “success” of core regions or the atypical success-stories in peripheral areas. In this context, the importance of transport infrastructure for improving the accessibility and competitiveness of peripheral regions is recognised in the context of the Structural Funds. The long-term structural effort needed to reduce disparities in terms of basic infrastructure, of which transport is a large part, is particularly reflected in the allocation of almost 1/3 of total EU funding to these types of measures (objective 1 areas). The purpose of this article is to provide a systematic analysis of the contribution and impact on centre-periphery convergence of the Structural Funds transport infrastructure actions, but also to discuss the possible evolution of the centre-periphery paradigm in the light of recent developments in economic development, cohesion and accessibility in European peripheral areas. Indeed, it seems as if infrastructure investments under the Structural Funds have actually been quite successful in reducing the gap between core and periphery. To understand why and how, we have to analyse the emergence of regional growth centres in peripheral areas. The article will argue that these regional growth centres play an increasingly important role in the definition of the centre-periphery concept as well as in challenging the traditional centre-periphery paradigm.